2021
DOI: 10.1088/2053-1583/abf234
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of large-scale two-dimensional semiconductors: challenges and developments

Abstract: Two-dimensional (2D) materials offer opportunities to explore both fundamental science and applications in the limit of atomic thickness. Beyond the prototypical case of graphene, other 2D materials have recently come to the fore. Of particular technological interest are 2D semiconductors, of which the family of materials known as the group-VI transition metal dichalcogenides (TMDs) has attracted much attention. The presence of a bandgap allows for the fabrication of high on-off ratio transistors and optoelect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(114 citation statements)
references
References 219 publications
(581 reference statements)
1
103
0
1
Order By: Relevance
“…In particular, the adoption of crystalline substrates (such as sapphire, GaN, and 4H-SiC) with the hexagonal basal plane and good lattice matching with MoS 2 is expected to enhance the domain size and electronic quality of the grown films. Furthermore, the homogeneous large area few-layer MoS 2 can be transferred to arbitrary substrates (including flexible ones) [68] and find applications in different fields of microelectronics, flexible electronics, and sensing.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the adoption of crystalline substrates (such as sapphire, GaN, and 4H-SiC) with the hexagonal basal plane and good lattice matching with MoS 2 is expected to enhance the domain size and electronic quality of the grown films. Furthermore, the homogeneous large area few-layer MoS 2 can be transferred to arbitrary substrates (including flexible ones) [68] and find applications in different fields of microelectronics, flexible electronics, and sensing.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the other underexplored challenge is the direct growth of high-quality single crystal 2D material on silicon devices that would require very high processing temperatures, which is not feasible. Although, CVD can enable largearea synthesis of 2D materials, the usual wet and dry methods of transferring CVD grown 2D materials onto device substrate do not currently meet the high-quality standards set by the semiconductor industry [196][197][198]. Recently Kim et al [199] have demonstrated the damage free transfer of graphene and MoS 2 by minimizing the instability-induced damage mechanism using optimal thickness of PDMS layer.…”
Section: Integration Of 2d Materials With Siliconmentioning
confidence: 99%
“…Исследование графеноподобных полупроводниковых кристаллов является одним из актуальных направлений в области современных материалов электронной техники [1][2][3][4][5]. К числу таких полупроводников относится моноселенид галлия (GaSe), состоящий из тетраслоев, внутри которых атомные слои в порядке Se-Ga-Ga-Se связаны ковалентно, в то время как отдельные тетраслои между собой связаны слабыми силами ван-дер-Ваальса.…”
Section: Introductionunclassified